2020
DOI: 10.46281/ijafr.v5i3.805
|View full text |Cite
|
Sign up to set email alerts
|

FINANCING HEIs THROUGH WAQF FUND IN BANGLADESH: ISSUES AND POSSIBILITIES

Abstract: The aim of the paper is to explicate the narrative of waqf fund for funding higher educational institutions (HEIs) in Bangladesh. nowadays, there is the reason for preventing students to pursue their higher education which is costly matters. This paper highlights some problems in implementing waqf fund for financing HEIs in Bangladesh and offer some Easier way to overcome this condition through the implementation of a waqf fund based HEIs. As a qualitative approach, data were gathered by conducting the intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Customer attitude to consider the bank's reputation is part of the service quality, and customers place equal emphasis on bank reputation and low service charges when selecting a bank [45,46]. Many studies have identified reputation as one of the important aspects to contemplate when choosing a bank [47][48][49]. Abdul-Kadir and Selamat [50] identified the three most important issues that influence a consumer's decision to use a bank.…”
Section: Reputationmentioning
confidence: 99%
See 1 more Smart Citation
“…Customer attitude to consider the bank's reputation is part of the service quality, and customers place equal emphasis on bank reputation and low service charges when selecting a bank [45,46]. Many studies have identified reputation as one of the important aspects to contemplate when choosing a bank [47][48][49]. Abdul-Kadir and Selamat [50] identified the three most important issues that influence a consumer's decision to use a bank.…”
Section: Reputationmentioning
confidence: 99%
“…Several studies have focused particularly on the Islamic banks and customer attitudes and behavioural intentions to engage in Islamic banking services [49]. Customers believe that Islamic financial literacy, ethical organisation, bank reputation, and religious values are the most crucial elements that influence the mindset of customers to receive services of Islamic banks [45,46].…”
Section: Attitudesmentioning
confidence: 99%